Towards bionic noses. Issue 2 (20th March 2017) - Persaud, Krishna Chandra
Abstract : Purpose: The purpose of this paper is to review recent progress in electronic nose technologies, focusing on hybrid systems combining biological elements with physical transducers. Design/methodology/approach: Electronic nose technologies are moving rapidly towards hybrid bioelectronic systems, where biological odour-recognition elements from the olfactory pathways of vertebrates and insects are being utilised to construct new "bionic noses" that can be used in industrial applications. Findings: With the increased understanding of how chemical senses and the brain function in biology, an emerging field of "neuromorphic olfaction" has arisen. Research limitations/implications: Important components are olfactory receptor proteins and soluble proteins found at the periphery of olfaction called odorant-binding proteins. The idea is that these proteins can be incorporated into transducers and function as biorecognition elements for volatile compounds of interest. Practical implications: Major drivers are the security, environmental and medical applications, and the internet of things will be a major factor in implementing low-cost chemical sensing in networked applications for the future. Social implications: Widespread take up of new technologies that are cheap will minimise the impact of environmental pollution, increase food safety and may potentially help in non-invasive screening for medical ailments. Originality/value: This review brings together diverse threads of research leading to a common theme that will inform a non-expert of recent developments in the field.